Calcium Oscillations Trigger Focal Adhesion Disassembly in Human U87 Astrocytoma Cells - Grégory Giannone; Philippe Rondé; Mireille Gaire; Jacques Haiech; Kenneth Takeda (2002)
Integrin-associated intracellular Ca2+ oscillations modulate cell migration, probably by controlling integrin-mediated release of the cell rear during migration. Focal adhesion kinase (FAK), via its tyrosine phosphorylation activity, plays a key role in integrin signaling. In human U87 astrocytoma cells, expression of the dominant negative FAK-related non-kinase domain (FRNK) inhibits the Ca2+-sensitive component of serum-dependent migration. We investigated how integrin-associated Ca2+signaling might be coupled to focal adhesion (FA) dynamics by visualizing the effects of Ca2+ spikes on FAs using green fluorescent protein (GFP)-tagged FAK and FRNK. We report that Ca2+ spikes are temporally correlated with movement and disassembly of FAs, but not their formation. FRNK transfection did not affect generation of Ca2+ spikes, although cell morphology was altered, with fewer FAs of larger size and having a more peripheral localization being observed. Larger sized FAs in FRNK-transfected cells were not disassembled by Ca2+ spikes, providing a possible explanation for impaired Ca2+-dependent migration in these cells. Stress fiber end movements initiated by Ca2+ spikes were visualized using GFP-tagged myosin light chain kinase (MLCK). Ca2+-associated movements of stress fiber ends and FAs had similar kinetics, suggesting that stress fibers and FAs move in a coordinated fashion. This indicates that increases in Ca2+ likely trigger disassembly of adhesive structures that involves disruption of integrin-extracellular matrix interactions, supporting a key role for Ca2+-sensitive inside-out signaling in cell migration. A rapid increase in tyrosine phosphorylation of FAK was found in response to an elevation in Ca2+ induced by thapsigargin, and we propose that this represents the initial triggering event linking Ca2+signaling and FA dynamics to cell motility. Integrin-associated intracellular Ca2+ oscillations modulate cell migration, probably by controlling integrin-mediated release of the cell rear during migration. Focal adhesion kinase (FAK), via its tyrosine phosphorylation activity, plays a key role in integrin signaling. In human U87 astrocytoma cells, expression of the dominant negative FAK-related non-kinase domain (FRNK) inhibits the Ca2+-sensitive component of serum-dependent migration. We investigated how integrin-associated Ca2+signaling might be coupled to focal adhesion (FA) dynamics by visualizing the effects of Ca2+ spikes on FAs using green fluorescent protein (GFP)-tagged FAK and FRNK. We report that Ca2+ spikes are temporally correlated with movement and disassembly of FAs, but not their formation. FRNK transfection did not affect generation of Ca2+ spikes, although cell morphology was altered, with fewer FAs of larger size and having a more peripheral localization being observed. Larger sized FAs in FRNK-transfected cells were not disassembled by Ca2+ spikes, providing a possible explanation for impaired Ca2+-dependent migration in these cells. Stress fiber end movements initiated by Ca2+ spikes were visualized using GFP-tagged myosin light chain kinase (MLCK). Ca2+-associated movements of stress fiber ends and FAs had similar kinetics, suggesting that stress fibers and FAs move in a coordinated fashion. This indicates that increases in Ca2+ likely trigger disassembly of adhesive structures that involves disruption of integrin-extracellular matrix interactions, supporting a key role for Ca2+-sensitive inside-out signaling in cell migration. A rapid increase in tyrosine phosphorylation of FAK was found in response to an elevation in Ca2+ induced by thapsigargin, and we propose that this represents the initial triggering event linking Ca2+signaling and FA dynamics to cell motility. stress fiber focal adhesion focal adhesion kinase focal adhesion-related non kinase domain extracellular matrix myosin light chain kinase calcium antibody monoclonal antibody green fluorescent protein yellow fluorescent protein Eagle's minimum essential medium 1,2-bis(2-aminophenoxy)ethane-N,N,N′,N′-tetraacetic acid tetrakis(acetoxymethyl ester) tetramethylrhodamine isothiocyanate fluorescein isothiocyanate phosphate-buffered saline analysis of variance Cell migration is a cyclic process involving initial protrusion of the leading edge, formation of adhesive sites, contraction of the cell body, and release of adhesive sites at the cell rear (1Lauffenburger D.A. Horwitz A.F. Cell. 1996; 84: 359-369Abstract Full Text Full Text PDF PubMed Scopus (3291) Google Scholar). Adhesive sites are dynamic membrane structures that vary in size and composition during migration. Integrins, actin stress fibers (SFs)1 and other structural proteins, and regulatory signaling molecules cluster at focal adhesions (2Burridge K. Chrzanowska-Wodnicka M. Annu. Rev. Cell Dev. Biol. 1996; 12: 463-518Crossref PubMed Scopus (1663) Google Scholar). Focal adhesions (FAs) serve as points of traction for contractile forces underlying forward cell movement and their dynamics are finely regulated. For example, FAs are highly motile in stationary fibroblasts but are largely stationary in migrating fibroblasts, thereby transducing contractile forces into movement (3Smilenov L.B. Mikhailov A. Pelham R.J. Marcantonio E.E. Gundersen G.G. Science. 1999; 286: 1172-1174Crossref PubMed Scopus (286) Google Scholar). This suggests the existence of a molecular clutch that couples cytoskeleton-mediated traction and cell contraction. Focal adhesion kinase (FAK) is activated and localized at FAs upon cell adhesion to the extracellular matrix (ECM; Refs. 4Schaller M.D. Parsons J.T. Curr. Opin. Cell Biol. 1994; 6: 705-710Crossref PubMed Scopus (495) Google Scholar and 5Schlaepfer D.D. Hauck C.R. Sieg D.J. Prog. Biophys. Mol. Biol. 1999; 71: 435-478Crossref PubMed Scopus (1036) Google Scholar). Given the abundance of FAs and the reduced migration of fibroblasts from FAK null mice (6Ilic D. Furuta Y. Kanazawa S. Takeda N. Sobue K. Nakatsuji N. Nomura S. Fujimoto J. Okada M. Yamamoto T. Nature. 1995; 377: 539-544Crossref PubMed Scopus (1591) Google Scholar), FAK is likely involved in FA remodeling during migration. FAK-related non-Kinase (FRNK), the non-catalytic C-terminal portion of FAK containing the FA targeting sequence, is also expressed as a separate dominant negative protein (7Richardson A. Parsons T.A. Nature. 1996; 380: 538-540Crossref PubMed Scopus (452) Google Scholar). The differential expression of FAK and FRNK is transcriptionally regulated, each of these proteins having distinct promoters within the FAK gene (8Nolan K. Lacoste J. Parsons J.T. Mol. Cell. Biol. 1999; 19: 6120-6129Crossref PubMed Scopus (97) Google Scholar). Although the function of endogenous FRNK is not clear, FRNK has been used to alter signaling via endogenous FAK. When overexpressed in cells, FRNK acts as a negative regulator of FAK activity, inhibiting phosphorylation of FAK and different FAK-related processes, including cell cycle progression (9Zhao J.H. Reiske H. Guan J.L. J. Cell Biol. 1998; 143: 1997-2008Crossref PubMed Scopus (302) Google Scholar, 10Taylor J.M. Mack C.P. Nolan K. Regan C.P. Owens G.K. Parsons J.T. Mol. Cell. Biol. 2001; 21: 1565-1572Crossref PubMed Scopus (143) Google Scholar), cell spreading on fibronectin (7Richardson A. Parsons T.A. Nature. 1996; 380: 538-540Crossref PubMed Scopus (452) Google Scholar, 11Richardson A. Malik R.K. Hildebrand J.D. Parsons T. Mol. Cell. Biol. 1997; 17: 6906-6914Crossref PubMed Scopus (290) Google Scholar), and migration (12Gu J. Tamura M. Pankov R. Danen E.H. Takino T. Matsumoto K. Yamada K.M. J. Cell Biol. 1999; 146: 389-403Crossref PubMed Scopus (376) Google Scholar, 13Sieg D.J. Hauck C.R. Schlaepfer D.D. J. Cell Sci. 1999; 112: 2677-2691Crossref PubMed Google Scholar). This suggests that the inhibitory effects of FRNK in migration might arise from altered FAK localization and phosphorylation. We and others reported that migration is dependent on Ca2+signaling in astrocytoma (14Rondé P. Giannone G. Gerasymova I. Stoeckel H. Takeda K. Haiech J. Biochim. Biophys. Acta. 2000; 1498: 273-280Crossref PubMed Scopus (33) Google Scholar), smooth muscle cells (15Scherberich A. Campos-Toimil M. Rondé P. Takeda K. Beretz A. J. Cell Sci. 2000; 113: 653-662Crossref PubMed Google Scholar), neutrophils (16Mandeville J.T. Ghosh R.N. Maxfield F.R. Biophys. J. 1995; 68: 1207-1217Abstract Full Text PDF PubMed Scopus (68) Google Scholar), and neurons (17Komuro H. Rakic P. Neuron. 1996; 17: 275-285Abstract Full Text Full Text PDF PubMed Scopus (353) Google Scholar). In cerebellar granule cells, Ca2+-dependent migration is correlated with the amplitude and frequency of Ca2+ spikes (17Komuro H. Rakic P. Neuron. 1996; 17: 275-285Abstract Full Text Full Text PDF PubMed Scopus (353) Google Scholar), which may regulate different steps during migration. Disruption of integrin-mediated adhesion involves Ca2+-sensitive proteins, including calpain (18Huttenlocher A. Palecek S.P., Lu, Q. Zhang W. Mellgren R.L. Lauffenburger D.A. Ginsberg M.H. Horwitz A.F. J. Biol. Chem. 1997; 272: 32719-32722Abstract Full Text Full Text PDF PubMed Scopus (340) Google Scholar, 19Dourdin N. Bhatt A.K. Dutt P. Greer P.A. Arthur J.S. Elce J.S. Huttenlocher A. J. Biol. Chem. 2001; 276: 48382-48388Abstract Full Text Full Text PDF PubMed Scopus (213) Google Scholar), myosin light chain kinase (MLCK; Ref. 20Eddy R.J. Pierini L.M. Matsumura F. Maxfield F.R. J. Cell Sci. 2000; 113: 1287-1298Crossref PubMed Google Scholar), and calcineurin (21Lawson M.A. Maxfield F.R. Nature. 1995; 377: 75-79Crossref PubMed Scopus (479) Google Scholar). These data indicate that Ca2+ signaling may be a component of the molecular clutch regulating transitions between stationary and non-stationary FAs. To test whether Ca2+ signaling affects FA organization, confocal microscopy was used to visualize simultaneously Ca2+ levels and dynamics of FAs or actin SFs in U87 cells expressing FA (FAK, FNRK) or cytoskeletal (MLCK) proteins tagged with GFP. We report that Ca2+ spikes trigger movement and disassembly of FAs. Although FRNK expression did not suppress Ca2+-dependent FA disassembly, more Ca2+-insensitive FAs having a larger surface were observed in FRNK cells. Our results provide an explanation linking FA disassembly to a temporally accurate cellular signal. Cell culture media (EMEM), fetal calf serum, HEPES, l-glutamine, penicillin, streptomycin, gentamycin, and trypsin-EDTA were from Invitrogen; Fura Red-AM, BAPTA-AM, and pluronic acid were from Molecular Probes; Matrigel and the monoclonal antibody (mAb) against FAK kinase domain were from Interchim; phalloidin-TRITC, mAb against the FAK C-terminal region (amino acids 1039–1052), and anti-MLCK mAb were from Sigma; the anti-Tyr397-phosphorylated FAK Ab was from BIOSOURCE; secondary horseradish peroxidase-conjugated Abs were from Promega; the FITC-labeled goat anti-mouse (GAM-FITC) Ab was from Zymed Laboratories Inc.. The human astrocytoma U87 cell line was obtained from the ATCC. Cells were maintained at 37 °C in a humidified incubator gassed with 5% CO2 in air on type I collagen (0.06 mg/ml)-coated plastic dishes in EMEM supplemented with 10% heat-inactivated fetal calf serum, 0.6 mg/ml glutamine, 200 IU/ml penicillin, 200 IU/ml streptomycin, and 0.1 mg/ml gentamycin. Fluorescent FA-targeted protein was made by fusion of FAK (human T lymphocyte pCDM8-FAK plasmid; Ref.40Whitney G.S. Chan P.Y. Blake J. Cosand W.L. Neubauer M.G. Aruffo A. Kanner S.B. DNA Cell Biol. 1993; 12: 823-830Crossref PubMed Scopus (91) Google Scholar) next to the 3′ end of "yellow Cameleon-2" (pcDNA3-Ycam2 plasmid; Ref. 22Miyawaki A. Llopis J. Heim R. McCaffery J.M. Adams J.A. Ikura M. Tsien R.Y. Nature. 1997; 388: 882-887Crossref PubMed Scopus (2650) Google Scholar). To allow fusion of FAK in continuity with the Ycam2 reading frame, the stop codon next to EYFP was replaced by a tyrosine codon (QuikChange, Stratagene). FAK cDNA was amplified by PCR using a 5′ primer containing a MfeI site and a 3′ primer containing a NheI site. The FAK PCR product was digested with MfeI and NheI and cloned in the corresponding compatible sites, EcoRI and XbaI, located in the multiple cloning site of the newly mutated pcDNA3-YCam2 vector, adjacent to EYFP, to give FAK-Ycam. To create FRNK-Ycam, the FRNK domain was amplified by PCR using pCDM8-FAK as template, a forward primer with an EcoRI site at the 5′ end of the glutamic acid codon 681 relative to the FAK start codon, and the same reverse primer as for FAK amplification, adding a NheI site. The PCR product was digested with EcoRI andNheI and cloned in-frame with the EYFP coding sequence in the EcoRI/XbaI compatible sites of the mutated pcDNA3-Ycam2 vector. The MLCK-210-GFP construct (24Kudryashov S.K. Chibalina M.V. Birukov K.G. Lukas T.J. Sellers J.R. Van Eldik L.J. Watterson D.M. Shirinsky V.P. FEBS Lett. 1999; 463: 67-71Crossref PubMed Scopus (35) Google Scholar) was in pEGFP vector (CLONTECH). All constructs were verified by sequencing. The plasmids were isolated (JetStar, Genomed) before transfection by electroporation. Cells (5 × 106) were resuspended at 108 cell/ml in EP buffer (in mm: 50 K2HPO4, 20 CH3CO2K, 20 KOH, pH 7.4). Plasmidic DNA (2 μg of construct-encoding plasmid, 8 μg of pBluescript) was diluted in 100 μl of EP buffer; 4 μl of 1m MgSO4 were added and incubated with 50 μl of cell suspension for 20 min at room temperature. The cell/DNA mixture was electroporated in a 0.4-cm cuvette (Bio-Rad Gene Pulser; 500 microfarads, 240 V). Cells were then placed in 10 ml of EMEM with 10% fetal calf serum in 80-mm2 dishes. Cells were selected 24 h later using 800 μg/ml G418 (Sigma) and maintained with 400 μg/ml G418. Cells were sorted to obtain >80% expressing cells using a flow cytometer (FACStar, Becton-Dickinson) before use. A wound-healing migration model was used, as described previously (15Scherberich A. Campos-Toimil M. Rondé P. Takeda K. Beretz A. J. Cell Sci. 2000; 113: 653-662Crossref PubMed Google Scholar). FAK-Ycam or FRNK-Ycam cells (2 × 105 cells/ml) were grown to confluence in Matrigel-coated (178 μg/ml) Petri dishes. After 24-h serum starvation, a rectangular lesion was made, cells were rinsed and incubated with medium with or without the tested compound. After 24 h of migration, three fields at the lesion border were acquired using a CCD camera (Panasonic) on an inverted microscope (Olympus IMT2, 10× phase objective). In each field, migration distance for the 10 most mobile cells was measured using Image Tool software (available by FTP from maxrad6.uthscsa.edu). For BAPTA experiments, cells were first loaded (45 min) with 20 μm BAPTA-AM in the incubator prior to creation of lesions. Intracellular Ca2+ was measured using Fura Red by confocal microscopy (Bio-Rad 1024, krypton-argon laser 488 nm; Nikon Eclipse TE300, 40× oil-immersion CFI Plan-Fluor n.a. 1.3 objective) alone or simultaneously with FA or SF dynamics. Cells (5 × 104 cells/ml) expressing FAK-Ycam, FRNK-Ycam, or MLCK-GFP were grown to subconfluence on Matrigel in Petri dishes in which a 2-cm diameter hole had been cut in the base and replaced by a thin (0.07 mm) coverslip (41Lynch J. Soares Lemos V. Bucher B. Stoclet J.C. Takeda K. J. Biol. Chem. 1994; 269: 8226-8233Abstract Full Text PDF PubMed Google Scholar). After 48 or 72 h, cells in culture medium were loaded with 10 μmFura Red-AM and 0.03% pluronic acid (45 min) in the incubator and then washed two times with Ringer solution (in mm: 140 NaCl, 5 KCl, 2 CaCl2, 2 MgCl2, 10 HEPES, 11 glucose, pH 7.4). Imaging of single cells in Ringer solution was done at 30 °C, at 585 ± 10 nm for Ca2+ alone, at 1-s intervals, usually for 15 min. For simultaneous measurements of Ca2+(at 585 nm) and FA (Ycam constructs) or SF (MLCK-GFP) dynamics, images at 522 ± 16 nm were acquired simultaneously every 10 s (EYFP) and 15 s (EGFP), usually for 30 min. Images were taken at the bottom cell surface. NIH Image software was used to assess FA surface areas and the dynamics of FAs and SFs. For FA size distributions, FAK-Ycam and FRNK-Ycam cells having similar expression levels were used. Fluorescent FAs were selected by thresholding using NIH Image. The same threshold was applied to all cells, corresponding FA pixel areas were calculated and converted to μm2. This analysis was done to determine the size of both immobile and motile, Ca2+-sensitive FAs. FA movement and disassembly triggered by a Ca2+ spike were visualized using a color overlay representation of three sequential images (3Smilenov L.B. Mikhailov A. Pelham R.J. Marcantonio E.E. Gundersen G.G. Science. 1999; 286: 1172-1174Crossref PubMed Scopus (286) Google Scholar). FAK-Ycam, FRNK-Ycam, or MLCK-GFP cells were plated at low density on Matrigel for 2 days and then treated or not with 1 μm thapsigargin. At the indicated time, cultures were washed with cold PBS and then incubated with lysis buffer (1% Triton-X100, 1% SDS, 100 mm NaF, 1 mmNa3VO4, 10 mmNaP2O7, in PBS, supplemented with an anti-protease mixture; Complete, Roche Molecular Biochemicals). Cell lysates were solubilized in Laemmli's buffer (5% glycerol, 2.5% β-mercaptoethanol, 1% SDS, 0.005% bromphenol blue, 50 mm Tris-HCl, pH 6.8) at 95 °C and resolved by SDS-PAGE (usually 5% polyacrylamide, but 8% for the blot used to separate FRNK and FAK) and then transferred to polyvinylidene difluoride membranes (Millipore). After blocking overnight at room temperature with 0.1% casein in PBS, 0.3% Tween, membranes were incubated 1.5 h with different Abs: anti-FAK kinase (immunogen corresponding to the kinase domain of FAK, amino acids 354–533) used at 1/1000 V/V dilution; anti-FAK Ct, (immunogen corresponding to the C-terminal region of FAK, amino acids 1039–1052) used at 1/4000; anti-Tyr397-phosphorylated FAK (1/4000) or anti-MLCK (1/10000), followed by 1-h exposure to either anti-rabbit IgG coupled to horseradish peroxidase (1/60,000) or anti-mouse IgG coupled to horseradish peroxidase (1/60,000). Specific staining was revealed using ECL kits (Amersham Biosciences). Blots were analyzed by densitometry. Band intensities of FAK and phosphorylated FAK were determined as (OD phosphorylated FAK/OD total FAK) × 100. For each condition, blots from four different experiments were analyzed. FAK-Ycam, FRNK-Ycam, or MLCK-GFP cells were rinsed with PBS and fixed 15 min with 3% paraformaldehye at room temperature. After three washes with PBS, cells were treated for 10 min with 0.2% Triton X-100 in PBS, 0.2% BSA and incubated 30 min with PBS, 3% BSA. Cells were washed three times with PBS, 0.2% BSA and incubated 1 h with either 1 μg/ml phalloidin-TRITC, the anti-MLCK mAb K36 (1/10000), or with the anti-FAK mAb (1/1000) in PBS, 0.2% BSA. For actin staining, the incubation buffer was removed and replaced by PBS, 0.2% BSA. For MLCK or FAK staining, cells were washed three times and incubated 1 h with a FITC-labeled goat anti-mouse Ab (GAM-FITC, 1/100). Fluorescence was observed using a confocal microscope and a 40× objective, as above. FITC and TRITC were excited at 488 and 568 nm, respectively, and fluorescence was collected at 522 and 585 nm. We reported that migration of U87 cells is associated with Ca2+ oscillations (14Rondé P. Giannone G. Gerasymova I. Stoeckel H. Takeda K. Haiech J. Biochim. Biophys. Acta. 2000; 1498: 273-280Crossref PubMed Scopus (33) Google Scholar), as intracellular Ca2+ buffering by BAPTA partly inhibits serum-dependent migration. To analyze the role of FAK in Ca2+-dependent migration, U87 cells were transfected with FAK or the dominant negative FRNK, fused to the fluorescent yellow Cameleon-2 (Ycam) tag, a fluorescence resonance energy transfer-based Ca2+ sensor containing CFP and EYFP (22Miyawaki A. Llopis J. Heim R. McCaffery J.M. Adams J.A. Ikura M. Tsien R.Y. Nature. 1997; 388: 882-887Crossref PubMed Scopus (2650) Google Scholar). Expression of FAK-Ycam or FRNK-Ycam did not alter endogenous FAK levels compared with controls (Fig.1 A, left). FRNK-Ycam expression (Fig. 1 A, right) was deduced by subtracting the endogenous FAK band from the band representing endogenous FAK plus FRNK-Ycam. Expression levels of FAK-Ycam and FRNK-Ycam were 1.5–2 times that of endogenous FAK. Compared with controls, serum-independent migration was unchanged in FAK- and FRNK-transfected cells, while serum-dependent migration decreased by 25% only in FRNK-transfected cells (Fig. 1 B,left), in agreement with previous studies (12Gu J. Tamura M. Pankov R. Danen E.H. Takino T. Matsumoto K. Yamada K.M. J. Cell Biol. 1999; 146: 389-403Crossref PubMed Scopus (376) Google Scholar). Buffering of intracellular Ca2+ with BAPTA did not affect serum-independent migration in control and transfected cells, but inhibited serum-dependent migration by 33% in FAK-Ycam cells. The lack of effect of BAPTA on serum-dependent migration of FRNK-transfected cells together with the clear inhibition by BAPTA in FAK-transfected and control cells indicate that the migration component inhibited by FRNK expression is mainly Ca2+-dependent. We found that Ca2+ spikes in U87 cells occur only in the presence of serum and are blocked by inhibitory antibodies against β1 and β3 integrin subunits, with the generation of such Ca2+ spikes depending on activation of phospholipase Cγ. 2P. Rondé, G. Giannone, A. Scherberich, A. Beretz, J. Haiech, and K. Takeda, submitted for publication. The FAK tyrosine 397 autophosphorylation site interacts with and activates phospholipase Cγ, representing a possible link between integrins and Ca2+ signaling (23Zhang X. Chattopadhyay A., Ji, Q.S. Owen J.D. Ruest P.J. Carpenter G. Hanks S.K. Proc. Natl. Acad. Sci. U. S. A. 1999; 96: 9021-9026Crossref PubMed Scopus (158) Google Scholar). Since FRNK contains the focal adhesion targeting sequence that is necessary and sufficient for FAK recruitment to FAs but lacks the phospholipase Cγ-interacting autophosphorylation site, FRNK-Ycam expression might inhibit Ca2+ oscillations. However, the frequency of Ca2+ spikes over 15 min in cells expressing FAK-Ycam or FRNK-Ycam was similar (Fig. 1 B,right) and not different compared with controls (not shown). For most FRNK-Ycam cells, the distribution of endogenous FAK at FAs, evaluated using an Ab against the FAK kinase domain, was unaltered (Fig. 1 C, left), as found previously (7Richardson A. Parsons T.A. Nature. 1996; 380: 538-540Crossref PubMed Scopus (452) Google Scholar). This suggests that sufficient endogenous FAK is expressed in most FRNK-transfected cells (Fig. 1 C), perhaps accounting for the unaltered generation of Ca2+ spikes (23Zhang X. Chattopadhyay A., Ji, Q.S. Owen J.D. Ruest P.J. Carpenter G. Hanks S.K. Proc. Natl. Acad. Sci. U. S. A. 1999; 96: 9021-9026Crossref PubMed Scopus (158) Google Scholar). Thus, the Ca2+-dependent migration defect of FRNK-Ycam cells is not due to decreased Ca2+ signaling. Since differences in Ca2+ signaling do not underlie impaired migration of FRNK-Ycam cells, possible effects of Ca2+ spikes on FAs were investigated by simultaneously measuring Ca2+ variations (using Fura Red) and FA dynamics (using EYFP fluorescence of FAK-Ycam and FRNK-Ycam) in migrating cells. Color overlays of three sequential images (Fig.2 A) distinguish immobile FAs (black) versus motile FAs (rainbow). Most FAs were immobile in FAK-Ycam cells irrespective of Ca2+ oscillations. Motile FAs were present in oscillatory and non-oscillatory cells, being often localized at one edge of a migrating cell (Fig. 2 A). FA movements were linear and usually resulted in FA disassembly, with EYFP fluorescence decreasing or disappearing (Fig. 2 B), while immobile FAs never disassembled. In many cases, FA movement and subsequent disassembly was triggered by a Ca2+ spike (Fig. 2 B). In oscillatory FAK-Ycam cells, such FA disassembly was temporally correlated with Ca2+ spikes for 64% (37/58) of motile FAs. For 19% of motile FAs (11/58), the Ca2+ oscillation frequency was too high to determine clearly a correlation, and for the remaining 17% (10/58), no correlation was found. This indicates that Ca2+ spikes were responsible for the dynamics of a subset of FAs. Somewhat surprisingly, FA disassembly in oscillatory FRNK-Ycam cells (Fig. 2, C and D) was also temporally correlated with a Ca2+ spike for 50% (35/70) of motile FAs; the Ca2+ oscillation frequency was too high to establish a correlation for 30% of FAs (21/70), and there was no correlation for the remaining 20% (14/70). In FAK-Ycam (Fig. 3; 45 FAs,n = 19 cells) and FRNK-Ycam cells (not shown; 30 FAs,n = 10 cells), we found no clear link between oscillatory (Fig. 3, A and B) versusnon-oscillatory (Fig. 3, C and D) Ca2+ behavior and formation of FAs (evaluated as EYFP fluorescence increases). For FAK-Ycam cells, 49% (22/45) of newly formed FAs were seen in oscillatory cells, while 51% (23/45) were not, as was also the case for FRNK-Ycam cells (not shown). Thus, unlike FA disassembly, Ca2+ spikes and FA formation were not obviously correlated. Strikingly, the number, size, and localization of FAs were different in FNRK-Ycam compared with FAK-Ycam cells (Fig. 4, A andB). FRNK-Ycam cells had 3-fold fewer FAs (25 ± 3/cell,n = 4 cells), which were larger (Fig. 4, Cand D) and more peripherally located compared with FAK-Ycam cells (74 ± 10 FAs/cell, n = 4). Morphometric analysis (ratio of longest to shortest cell lengths) showed that FRNK-Ycam cells were more elongated (3.0 ± 0.2,n = 51) than FAK-Ycam cells (2.3 ± 0.1,n = 69), suggesting that they are more strongly held to the ECM. Comparison of the Ca2+ dependence of FA dynamics revealed that the size distribution of motile Ca2+-sensitive FAs (Fig. 4 E) mirrors that of all FAs in FAK-Ycam cells (Fig. 4 C). In contrast, in FRNK-Ycam cells, the size distribution of motile, Ca2+-sensitive FAs (Fig. 4 F) is not the same as for all FAs (Fig.4 D), with smaller FAs being preferentially disassembled by Ca2+ spikes. This may explain impaired Ca2+-dependent migration in FRNK-Ycam cells, as larger, immobile Ca2+-insensitive FAs would remain attached to the ECM despite oscillatory Ca2+ signaling. Since FAK regulates FA dynamics (5Schlaepfer D.D. Hauck C.R. Sieg D.J. Prog. Biophys. Mol. Biol. 1999; 71: 435-478Crossref PubMed Scopus (1036) Google Scholar, 6Ilic D. Furuta Y. Kanazawa S. Takeda N. Sobue K. Nakatsuji N. Nomura S. Fujimoto J. Okada M. Yamamoto T. Nature. 1995; 377: 539-544Crossref PubMed Scopus (1591) Google Scholar), and Ca2+ spikes trigger FA disassembly, this may be related to FAK activity. Therefore, FAK tyrosine phosphorylation was evaluated after thapsigargin-induced Ca2+ elevation (14Rondé P. Giannone G. Gerasymova I. Stoeckel H. Takeda K. Haiech J. Biochim. Biophys. Acta. 2000; 1498: 273-280Crossref PubMed Scopus (33) Google Scholar). Increases in Tyr397 phosphorylation of endogenous FAK and FAK-Ycam were detected within 30 s after 1 μm thapsigargin treatment (Fig. 5 A). After 1 min, phosphorylation was maximal (73% increase above control; Fig.5 B). Thus, rapid phosphorylation of FAK in response to Ca2+ increases provides a possible link between FA movements and Ca2+ spikes, supporting that these are regulatory events in migration. As FA disassembly involves disruption of ECM-integrin and/or SF-integrin interactions, we simultaneously followed the dynamics of SF ends and Ca2+ signals using MLCK-GFP-transfected cells (Fig. 6). No differences were found in the localization, distribution, and expression of MLCK in MLCK-GFP cells compared with controls (Fig. 6,A and B), as reported previously (24Kudryashov S.K. Chibalina M.V. Birukov K.G. Lukas T.J. Sellers J.R. Van Eldik L.J. Watterson D.M. Shirinsky V.P. FEBS Lett. 1999; 463: 67-71Crossref PubMed Scopus (35) Google Scholar). Moreover, the MLCK-GFP construct used here has the same activity in phosphorylating the 20-kDa regulatory light chain kinase when compared with endogenous MLCK (25Poperechnaya A. Varlamova O. Lin P.-J. Stull J.T. Bresnick A.R. J. Cell Biol. 2000; 151: 697-708Crossref PubMed Scopus (89) Google Scholar). Evaluation of SF end dynamics (using MLCK-GFP fluorescence; Fig. 6 C) and Ca2+variations (using Fura Red) revealed that SF end movements were triggered by a Ca2+ spike (Fig. 6 D). The average latency between a Ca2+ spike and SF end movement was 28 ± 6 s, with a rate of movement of 0.25 ± 0.04 μm/min (n = 21 SFs, 6 cells; Fig.7). These SF kinetic parameters were compared with those for motile Ca2+-sensitive FAs in FAK-Ycam and FRNK-Ycam cells (Fig.7 C). The latency between Ca2+ spikes and the onset of FA movement was 33 ± 5 s in FAK-Ycam cells (n = 21 FAs, 8 cells) and 31 ± 5 s in FRNK-Ycam cells (n = 35 FAs; 14 cells), with a FA speed of 0.18 ± 0.02 and 0.22 ± 0.02 μm/min, respectively. These kinetic parameters were not different, suggesting that Ca2+ spikes trigger coordinated movement of SF-associated FA complexes. This implies that during cell migration, Ca2+signaling results in disruption of ECM-integrin interactions rather than a decrease in FA-cytoskeletal interactions. We investigated the implication of intracellular Ca2+elevations in FA dynamics during migration of U87 astrocytoma cells. During oscillatory Ca2+ signaling, single Ca2+spikes triggered FA disassembly and subsequent cell edge retraction. In FRNK-Ycam cells, smaller sized FAs were more sensitive to Ca2+-triggered disruption compared with large FAs, consistent with FA stability being a limiting factor in motility. FAK phosphorylation was rapidly induced by a Ca2+ increase, indicating that FAK is a Ca2+ target during migration. Analysis of FA and SF kinetic parameters suggests that Ca2+signaling coordinates disruption of ECM-integrin interactions at FAs. Cell migration includes phases of protrusion, adhesion, and retraction (1Lauffenburger D.A. Horwitz A.F. Cell. 1996; 84: 359-369Abstract Full Text Full Text PDF PubMed Scopus (3291) Google Scholar), involving, respectively, formation, strengthening, and disassembly of focal contacts. FAK plays an important role in the dynamics of cell adhesion, but is not required for FA formation beneath lamellipodia of migrating cells (26Burridge K. Chrzanowska-Wodnicka M. Zhong C. Trends Cell Biol. 1997; 7: 342-347Abstract Full Text PDF PubMed Scopus (198) Google Scholar). FAK aggregates to clustered integrin receptors with or without ligand occupancy (27Miyamoto S. Akiyama S.K. Yamada K.M. Science. 1995; 267: 883-885Crossref PubMed Scopus (791) Google Scholar), consistent with FAK localization to FAs being an early or late event in the cascade of interactions, respectively, leading to formation or disruption of integrin-cytoskeletal linkages. This justifies our choice of FAK-Ycam (22Miyawaki A. Llopis J. Heim R. McCaffery J.M. Adams J.A. Ikura M. Tsien R.Y. Nature. 1997; 388: 882-887Crossref PubMed Scopus (2650) Google Scholar) as a probe for FA dynamics, indirectly allowing detection of clustered integrins. FAK-Ycam and FRNK-Ycam were localized to newly forming, punctate structures in protrusive areas, further supporting their use to follow indirectly integrin association/dissociation in FAs. As suggested previously (28Rottner K. Hall A. Small J.V. Curr. Biol. 1999; 9: 640-648Abstract Full Text Full Text PDF PubMed Scopus (514) Google Scholar), these punctate structures very probably are focal complexes, putative precursors of FAs. FAK tyrosine kinase activity is involved in the regulation FA turnover (29Ren X.D. Kiosses W.B. Sieg D.J. Otey C.A. Schlaepfer D.D. Schwartz M.A. J. Cell Sci. 2000; 113: 3673-3678Crossref PubMed Google Scholar). In FAK-deficient cells, reduced motility is accompanied by an increased number of FAs (6Ilic D. Furuta Y. Kanazawa S. Takeda N. Sobue K. Nakatsuji N. Nomura S. Fujimoto J. Okada M. Yamamoto T. Nature. 1995; 377: 539-544Crossref PubMed Scopus (1591) Google Scholar). FRNK expression inhibits integrin-stimulated migration and phosphorylation of endogenous FAK and other FA components such as paxillin and tensin (7Richardson A. Parsons T.A. Nature. 1996; 380: 538-540Crossref PubMed Scopus (452) Google Scholar, 11Richardson A. Malik R.K. Hildebrand J.D. Parsons T. Mol. Cell. Biol. 1997; 17: 6906-6914Crossref PubMed Scopus (290) Google Scholar, 13Sieg D.J. Hauck C.R. Schlaepfer D.D. J. Cell Sci. 1999; 112: 2677-2691Crossref PubMed Google Scholar). Thus, FAK phosphorylation likely governs FA dynamics and, hence, motility. In FAK-Ycam cells, FA morphology was similar to controls, and as found in previous studies using FAK-transfected U87 cells (12Gu J. Tamura M. Pankov R. Danen E.H. Takino T. Matsumoto K. Yamada K.M. J. Cell Biol. 1999; 146: 389-403Crossref PubMed Scopus (376) Google Scholar), migration was unchanged, unlike in Chinese hamster ovary cells where migration increased after FAK overexpression (30Cary L.A. Chang J.F. Guan J.L. J. Cell Sci. 1996; 109: 1787-1794Crossref PubMed Google Scholar). Expression of FRNK-Ycam induced elongated morphology and a sparse and peripheral distribution of enlarged FAs. Much evidence supports that defective FAK signaling leads to enlarged FAs. Cells expressing a kinase-deficient mutant of Src have larger FAs and reduced migration (31Fincham V.J. Frame M.C. EMBO J. 1998; 17: 81-92Crossref PubMed Scopus (264) Google Scholar). The interaction and activation of Src occurs at the FAK autophosphorylation site, which is absent for FRNK (11Richardson A. Malik R.K. Hildebrand J.D. Parsons T. Mol. Cell. Biol. 1997; 17: 6906-6914Crossref PubMed Scopus (290) Google Scholar). Src kinase activity weakens integrin-cytoskeletal linkages (32Felsenfeld D.P. Schwartzberg P.L. Venegas A. Tse R. Sheetz M.P. Nat. Cell Biol. 1999; 1: 200-206Crossref PubMed Scopus (233) Google Scholar) and may stimulate FA turnover by favoring lateral diffusion of integrins away from FAs. Thus, reduced FA dynamics leading to enlarged FAs is consistent with decreased migration of FRNK-Ycam cells. The disassembly of large FAs in FRNK-Ycam cells was Ca2+-insensitive, possibly because for this subset of FAs, endogenous FAK levels were small compared with FRNK levels. Our data support that FA size affects migration by also reflecting the Ca2+ sensitivity of FAs and, hence, their remodeling. FA disassembly involves disruption of ECM-integrin and/or integrin-cytoskeleton interactions, which are regulated by several calciproteins. For instance, contractile force activation via Ca2+/calmodulin-dependent MLCK may strengthen integrin-cytoskeletal linkages (26Burridge K. Chrzanowska-Wodnicka M. Zhong C. Trends Cell Biol. 1997; 7: 342-347Abstract Full Text PDF PubMed Scopus (198) Google Scholar) and is necessary for Ca2+-dependent migration of neutrophils (20Eddy R.J. Pierini L.M. Matsumura F. Maxfield F.R. J. Cell Sci. 2000; 113: 1287-1298Crossref PubMed Google Scholar). Conversely, integrin-cytoskeletal linkages are disrupted by calpain, a Ca2+-dependent protease, and calpain inhibition or disruption mimics the effects of FRNK expression on FA morphology (18Huttenlocher A. Palecek S.P., Lu, Q. Zhang W. Mellgren R.L. Lauffenburger D.A. Ginsberg M.H. Horwitz A.F. J. Biol. Chem. 1997; 272: 32719-32722Abstract Full Text Full Text PDF PubMed Scopus (340) Google Scholar, 19Dourdin N. Bhatt A.K. Dutt P. Greer P.A. Arthur J.S. Elce J.S. Huttenlocher A. J. Biol. Chem. 2001; 276: 48382-48388Abstract Full Text Full Text PDF PubMed Scopus (213) Google Scholar). Calreticulin appears to be essential for integrin-mediated Ca2+ signaling and adhesion (33Coppolino M.G. Woodside M.J. Demaurex N. Grinstein S., St- Arnaud R. Dedhar S. Nature. 1997; 386: 843-847Crossref PubMed Scopus (348) Google Scholar, 34Kwon M.S. Park C.S. Choi K. Ahnn J. Kim J.I. Eom S.H. Kaufman S.J. Song W.K. Mol. Biol. Cell. 2000; 11: 1433-1443Crossref PubMed Scopus (104) Google Scholar). Calcineurin, a protein phosphatase, is involved in integrin recycling to the front of migrating neutrophils (21Lawson M.A. Maxfield F.R. Nature. 1995; 377: 75-79Crossref PubMed Scopus (479) Google Scholar), probably via affinity modulation. We show that Ca2+ spikes trigger FA disassembly and propose that ECM-integrin linkages are disrupted, given the identical kinetic parameters for FA and SF dynamics, which suggests coordinated FA/SF movement. In agreement, in migrating fibroblasts, FAs move with a similar speed of 0.12 ± 0.08 μm/min and remain associated with SFs in retractile edges (3Smilenov L.B. Mikhailov A. Pelham R.J. Marcantonio E.E. Gundersen G.G. Science. 1999; 286: 1172-1174Crossref PubMed Scopus (286) Google Scholar). Our observation of linearly disassembling FAs suggests that FAK-Ycam and FRNK-Ycam remained linked to SF ends until complete disassembly. However, because integrin-cytoskeleton and integrin-ECM interactions are intimately related, linkage perturbations initiated at either side of these molecular complexes could be transmitted via modulation of integrin affinity/avidity to both intracellular and extracellular partners. For example, integrin ligation initiates recruitment of a cytoskeletal actin component (27Miyamoto S. Akiyama S.K. Yamada K.M. Science. 1995; 267: 883-885Crossref PubMed Scopus (791) Google Scholar) and linkage with the forward moving actin cytoskeleton (35Felsenfeld D.P. Choquet D. Sheetz M.P. Nature. 1996; 383: 438-440Crossref PubMed Scopus (196) Google Scholar). Conversely, detachment of integrins from the actin cytoskeleton may induce decreased integrin affinity/avidity for their ECM ligands (36Hughes P.E. Pfaff M. Trends Cell Biol. 1998; 8: 359-364Abstract Full Text Full Text PDF PubMed Scopus (383) Google Scholar,37Nishizaka T Shi Q. Sheetz M.P. Proc. Natl. Acad. Sci. U. S. A. 2000; 97: 692-697Crossref PubMed Scopus (68) Google Scholar). The cell migration process implies asymmetric signal transduction that directs cell polarization (1Lauffenburger D.A. Horwitz A.F. Cell. 1996; 84: 359-369Abstract Full Text Full Text PDF PubMed Scopus (3291) Google Scholar). In U87 astrocytoma cells, we observed spatially localized disassembly and formation of FAs, illustrating this asymmetry. Since FA disassembly but not formation was temporally correlated with Ca2+ spikes, Ca2+ signaling and/or regulatory Ca2+ target proteins may be spatially restricted to discrete subcellular compartments (38Hahn K. DeBiasio R. Taylor D.L. Nature. 1992; 359: 736-738Crossref PubMed Scopus (151) Google Scholar, 39Pettit E.J. Hallett M.B. J. Cell Sci. 1996; 109: 1689-1694PubMed Google Scholar). We are currently investigating compartmentalized Ca2+ signaling in migrating cells using our Ycam constructs as local detectors of Ca2+ near FAs. That a single Ca2+ spike is sufficient to trigger FA disassembly agrees with initiation of a regenerative process leading to irreversible FA disruption. The Ca2+-triggered event might transiently increase FAK signaling, perhaps followed by a Ca2+-independent process. This implies a latency between the Ca2+ spike and cell edge retraction resulting from FA disassembly. Consistent with our data, Ca2+ elevation and increased migration speed were positively correlated in neutrophils (16Mandeville J.T. Ghosh R.N. Maxfield F.R. Biophys. J. 1995; 68: 1207-1217Abstract Full Text PDF PubMed Scopus (68) Google Scholar), but since there was a 20-s delay between Ca2+elevation and increased motility, Ca2+ was proposed not to be the immediately causal signal. However, we show that FA disassembly begins 30 s after a Ca2+ spike, and once triggered, several minutes are required for complete disassembly. This supports that Ca2+ elevation is a proximal signal leading to increased motility. Finally, rapid thapsigargin-induced FAK Tyr397 phosphorylation agrees with Ca2+-dependent FAK activation being an initial event associated with FA disassembly. We thank R. Y. Tsien (University of California at San Diego), S. B. Kanner (Bristol Myers Squibb), and A. Bresnick and D. M. Watterson (Northwestern University) for generously providing Y-Cam-2, FAK, and MLCK-GFP plasmids, respectively.